The Impact of Corporate Governance Attributes on Financial Distress among the Listed Firms in Pharmaceuticals Industry of Bangladesh - Begum, Mst. Maksuda; Sarker, Niluthpaul; Nahar, Shamsun (International Journal of Economics and Financial Issues, 2023)
This paper investigates the relationship between corporate governance and the likelihood of financial distress. To evaluate the impact of corporate governance on financial distress, a multiple regression model and longitudinal panel data are used. Corporate governance is determined by the board of directors, audit committee, and ownership structure, whereas the Altman Z-score is used to indicate financial distress. The findings imply that financial distress is influenced by corporate governance variables (board independence, auditor independence, auditor opinion, sponsor directors ownership, and foreign shareholders), and firm-level variables (sales growth, performance, liquidity, firm size)). From an academic standpoint, this paper adds to our understanding of the association between corporate governance practices and the risk of financial distress in emerging markets like Bangladesh. The findings may encourage Bangladeshi listed companies to follow and implement good corporate governance practices, increasing investor, regulator, and stakeholder confidence.